Educational Philosophies: Behaviorism and Progressivism in the Context of Modern Christian Religious Education - Kawa, Simson Mau; Tanono, Solly Rosalia; Oematan, Senia Enjelika; Polli, Siska (Lembaga Penelitian dan Pendidikan Mandala, 2026)
In the dynamic era of modern education, the educational philosophy of behaviorism and progressivism offers a different approach that remains relevant in the modern education system (Khosiah et al., 2024). Behaviorism, pioneered by John Watson and B.F. Skinner, considers learning as a change in behavior due to stimulus and response. In practice, students are trained through repeated practice, rewards for positive actions, and definite assessment of results. This research is used to learn more about standardized tests, digital learning platforms and competency-based curricula to develop students' basic skills such as reading, writing and arithmetic. On the other hand, progressivism pioneered by John Dewey emphasized learning through direct experience and children's interests. Children learn by doing projects, having group discussions, and solving everyday problems. The teacher's role is more as a guide, not just delivering material, so that students can grow creative, independent, and able to work together in a democratic environment. Thus, in the current Indonesian educational context, for example in the Independent Curriculum, it can be seen that these two streams complement each other (Parwati, 2023). Therefore, behaviorism can help education achieve learning outcomes through technology, while progressivism encourages learning based on local culture, group work and character development. This combination prepares students to face the digital world, work challenges, and a harmonious and inclusive society.